Wedlock of the Gods - Sofola, Zulu (Evans Brothers Ltd, 1972)
Wedlock of the Gods is a tragedy which finds its roots in the ritual of death and mourning. The traditional solemnity of the ritual is distorted however for, rather than engaging in the normal funeral rites and rituals which should have cleansed her and sent the spirit of the deceased to the world of the gods, the widow expresses a sense of liberation from unwanted marriage, while the mother of the diseased performs rites meant to destroy her son's widow as an act of vengeance for supposedly killing her son.
Keywords: Drama